Implementasi Sistem Absensi Berbasis Web dengan Pendekatan UI/UX pada SMAN 2 Palembang - Dwi Bayu Laksana Rahmadani; Dimas Fendriansyah (Universitas Multi Data Palembang, 2026)
Attendance processes in schools are still commonly conducted manually, which may lead to recording errors, delayed data recapitulation, and low administrative efficiency. This study aims to implement a web-based attendance system with a focus on user interface (UI) and user experience (UX) design at SMAN 2 Palembang. The system was developed using a simplified Rational Unified Process (RUP) methodology consisting of four main phases: inception, elaboration, construction, and transition. The implementation results indicate that the system supports digital attendance processes through a simple, consistent, and user-friendly interface. The main features include user authentication, student data management, attendance recording, and attendance report generation. Functional testing results show that all core features operate according to system requirements and facilitate easier attendance data management. This system is expected to support the digitalization of attendance administration processes in the school environment.